Broadening of acoustic repertoire in Pomacentridae: tonal sounds in the Ambon damselfish Pomacentrus amboinensis. (20th August 2016) - Parmentier, E.; Frédérich, B.
Abstract: Damselfish are prolific callers, identified as being able to produce different kinds of sounds (pops and chirps) associated with various behaviors. During courtship and chase behaviors, the coral reef damselfish Pomacentrus amboinensis produces a previously unknown additional kind of call that we have named the wiping sound. These calls have two to three long (54 ± 13 ms) units that do not show the usual percussive aspect of the pomacentrid sounds. Calls consist of a high‐pitched (from 550 to 775 Hz) tonal sound in which the cycle repetition rate corresponds to the peak frequency. The high frequency of this tonal sound can be excluded as coming from the contraction of sound producing muscles. These sounds could be the result of a mechanism that drives the merging of successive pops. In the noisy environment of coral reefs and the resulting competition for acoustic space, the wiping sounds appear to be a good way to increase signal distinctiveness and opportunities for correct signal discrimination. This new kind of sound supports that acoustic communication is highly important in the biology of damselfishes and their diversification. Abstract : Damselfish are prolific callers. During courtship and chase behaviors, the damselfish Pomacentrus amboinensis produces a previously unknown kind of tonal call that we have named the wiping sound because it does not show the usual percussive aspect of the pomacentrid sounds. The high frequency (from 550 to 775 Hz) of this tonal sound can be excluded as coming from the contraction of sound producing muscles. The wiping sounds appear to be a good way to increase signal distinctiveness and opportunities for correct signal discrimination.